2014
DOI: 10.1038/pr.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Deficits of brainstem and spinal cord functions after neonatal hypoxia–ischemia in mice

Abstract: Background: Perinatal cerebral hypoxia-ischemia (HI) can lead to severe neurodevelopmental disorders. Studies in humans and animal models mainly focused on cerebral outcomes, and little is known about the mechanisms that may affect the brainstem and the spinal cord. Dysfunctions of neuromodulatory systems, such as the serotonergic (5-HT) projections, critical for the development of neural networks, have been postulated to underlie behavioral and motor deficits, as well as metabolic changes. Methods: The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In this model, a selective, significant decrease in numbers of 5-HT-positive neurons was noted in rostral raphe nuclei (dorsal raphe), while there was no change in the caudal raphe nuclei projecting to spinal cord, such as raphe magnus (Reinebrant et al 2010), similar to observation in a mouse model of neonatal asphyxia (Takeuchi et al 1992). Recently, increased levels of spinal serotonin, similar to our study, have been reported after unilateral carotid ligation and hypoxia in neonatal mice (Bellot et al 2014). Rodent models of perinatal brain injury, however, do not produce overt motor deficits and muscle hypertonia as in our rabbit model.…”
Section: Discussionsupporting
confidence: 91%
“…In this model, a selective, significant decrease in numbers of 5-HT-positive neurons was noted in rostral raphe nuclei (dorsal raphe), while there was no change in the caudal raphe nuclei projecting to spinal cord, such as raphe magnus (Reinebrant et al 2010), similar to observation in a mouse model of neonatal asphyxia (Takeuchi et al 1992). Recently, increased levels of spinal serotonin, similar to our study, have been reported after unilateral carotid ligation and hypoxia in neonatal mice (Bellot et al 2014). Rodent models of perinatal brain injury, however, do not produce overt motor deficits and muscle hypertonia as in our rabbit model.…”
Section: Discussionsupporting
confidence: 91%
“…[42] Disruption of the brainstem and spinal cord serotonergic system has also been proposed to account for the motor defects observed in neonatal mice using the Rice– Vanucci hypoxic-ischemic injury model. [43] Future studies in our UCO model investigating damaged neural pathways, such as serotonergic system pathway, after neonatal HIE may reveal cellular mechanisms of axonal degeneration relevant to the development of CP.…”
Section: Discussionmentioning
confidence: 99%
“…The exact causes of the changes in MN physiology observed here are unclear, but they could result from the increase in spinal monoamines that occurs after developmental HI injury in both rodents and rabbits (Bellot et al, 2014;Drobyshevsky et al, 2015). Serotonin is generally thought of as a neurotransmitter and neuromodulator, but developmental disruption in 5HT is associated with neurological disorders including autism, Rett syndrome, Down's syndrome and, more recently, CP (Bar-Peled et al, 1991;Whittle et al, 2007;Bellot et al, 2014;Yang et al, 2014;De Filippis et al, 2015;Drobyshevsky et al, 2015;Muller et al, 2016;Wirth et al, 2017). Serotonin increases MN excitability in neonatal and juvenile mice, rats and guinea pigs (Wang and Dun, 1990;Ziskind-Conhaim et al, 1993;Hsiao et al, 1997Hsiao et al, , 1998, and likely has the same effect on rabbit MNs.…”
Section: Neuromodulationmentioning
confidence: 95%
“…It's been shown in previous studies that HI injury during late gestation in rabbits can result in a variety of neurologic and muscular damage, including muscle stiffness (Derrick et al, 2004), loss of neurons in cortical layers 3 and 5, white matter injury, thinning of the corticospinal tract (Buser et al, 2010), cell death in the spinal cord and decreased numbers of spinal MNs (Drobyshevsky and Quinlan, 2017), increased sarcomere length, decreased muscle mass and hyperreflexia (Synowiec et al, 2019). There is also an increase in spinal monoamines which could increase the excitability of spinal neurons and thus promote spasticity (Bellot et al, 2014;Drobyshevsky et al, 2015). Thus, changes observed in spinal MNs in the rabbit model could be directly compared to motor deficits.…”
Section: Introductionmentioning
confidence: 99%